A novel MPPT method for enhancing energy conversion efficiency taking power smoothing into account. (1st September 2015) - Liu, Jizhen; Meng, Hongmin; Hu, Yang; Lin, Zhongwei; Wang, Wei
Highlights: We discuss the disadvantages of conventional OTC MPPT method. We study the relationship between enhancing efficiency and power smoothing. The conversion efficiency is enhanced and the volatility of power is suppressed. Small signal analysis is used to verify the effectiveness of proposed method. Abstract: With the increasing capacity of wind energy conversion system (WECS), the rotational inertia of wind turbine is becoming larger. And the efficiency of energy conversion is significantly reduced by the large inertia. This paper proposes a novel maximum power point tracking (MPPT) method to enhance the efficiency of energy conversion for large-scale wind turbine. Since improving the efficiency may increase the fluctuations of output power, power smoothing is considered as the second control objective. A T-S fuzzy inference system (FIS) is adapted to reduce the fluctuations according to the volatility of wind speed and accelerated rotor speed by regulating the compensation gain. To verify the effectiveness, stability and good dynamic performance of the new method, mechanism analyses, small signal analyses, and simulation studies are carried out based on doubly-fed induction generator (DFIG) wind turbine, respectively. Study results show that both the response speed and the efficiency of proposed method are increased. In addition, the extra fluctuations of output power caused by the high efficiency are reduced effectively by the proposed method with FIS.